1998
DOI: 10.3354/ame016081
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of high molecular weight dextran by the dinoflagellate Alexandrium catenella

Abstract: Carbohydrate macromolecules (dextrans) labeled with fluorescein isothiocyanate (FITC) were taken up by the dlnoflagellate Aiexandriurn catenella at a substrate concentration of 5 nlg C 1-'. The FITC-labeled dextrans appeared in what resembled food vacuoles inside the dinoflagellate cells. Between 5 and 50% of the cells contained fluorescent green vacuoles. A. catenella took up dextrans of high nlolecular weight (2000 kDa) but did not show significant uptake of lower molecular weight (20 kDa) dextrans. The upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 13 publications
(18 reference statements)
3
45
0
Order By: Relevance
“…Dinoflagellates have been shown to possess compensatory strategies to compete with fast-growing phytoplankton groups, such as allelopathy, mixotrophy, and internal nutrient storages (Legrand and Carlsson, 1998;Collos et al, 2004;Tillmann et al, 2008). B. baltica has recently been confirmed to effectively suppress growth of co-occurring diatoms by excretion of allelochemicals (Suikkanen et al, 2011), and utilization of residual P has been suggested to facilitate sustained growth of B.baltica in the 2004 mesocosms (Kremp et al, 2008).…”
Section: Dominance Patterns In Experimental Communitiesmentioning
confidence: 99%
“…Dinoflagellates have been shown to possess compensatory strategies to compete with fast-growing phytoplankton groups, such as allelopathy, mixotrophy, and internal nutrient storages (Legrand and Carlsson, 1998;Collos et al, 2004;Tillmann et al, 2008). B. baltica has recently been confirmed to effectively suppress growth of co-occurring diatoms by excretion of allelochemicals (Suikkanen et al, 2011), and utilization of residual P has been suggested to facilitate sustained growth of B.baltica in the 2004 mesocosms (Kremp et al, 2008).…”
Section: Dominance Patterns In Experimental Communitiesmentioning
confidence: 99%
“…It is possible that the species, like other bloomforming dinoflagellates, possesses compensatory strategies such as mixotrophy or utilization of dissolved organic nutrients and internal nutrient storages (Legrand & Carlsson 1998, Dyhrman & Anderson 2003, Collos et al 2004. Also, the role of P and, accordingly, N:P ratios needs to be examined more thoroughly.…”
Section: Effects Of Nutrient Availability On Phytoplankton Compositiomentioning
confidence: 99%
“…HMW polymeric compounds such as HS are too large to pass the cytoplasmic membrane (Payne 1980) and must be degraded enzymatically before uptake (Raven 1980), or taken up actively via pinocytosis, a mechanism in which the plasma membrane extends and forms a vesicle enclosing liquid containing the HMW compounds (Klut et al 1987); this mechanism has so far been very little studied and the importance of it for phytoplankton nutrition is virtually unknown. However, Legrand & Carlsson (1998) recently showed that the dinoflagellate Alexandrium catenella could take up large (2000 kDa) fluorescein isothiocyanate (F1TC)-labeled dextrans, presumably by pinocytosis.…”
Section: Introductionmentioning
confidence: 99%